The effective correlation time τ in jaw cysts determined from 400 MHz NMR T1 and T2 measurements. Issue 4 (2006) - Budak Budak, Hatice Hatice; Köylü Köylü, M. Zafer M. Zafer; Yilmaz Yilmaz, U. Nezih U. Nezih
Abstract : Macromolecular crowding is a general phenomenon of biological systems, and the evaluation of a correlation time for a specific molecule is difficult when the molecular crowding exists. The determination of an effective correlation time may therefore give useful insights into molecular dynamics of such systems. In this work, the relaxation rates in the mixture of D2 O (80%) and cystic fluid (20%) were measured with a NMR operating at 400 MHz for three types of cysts (non-infected radicular, infected radicular and hemorrhagic). The effective correlation times ( τ values) were then determined by using a formula derived from the observed relaxation rates. The τ value of the infected cyst was found to be longer than those of the others for the studied cases. The present data suggest that an effective correlation time for fluids with macromolecular crowding can be determined from NMR relaxation measurements.